Retaliation in rebellion: the missing link to explaining insurgent violence in Dagestan - Ratelle, Jean-François (Terrorism and political violence, 2017)
This article posits that the remnants of archaic sociocultural norms, particularly the honour-imposed custom of retaliation, play a crucial role in the process of insurgent engagement in Russia's autonomous republic of Dagestan. Through a series of interviews with former insurgents, this study outlines two retaliation-centred mechanisms: “individual retaliation” and “spiritual retaliation” in order to explain the microcosm of motives behind insurgent activity in Dagestan. In doing so, this study problematizes the role of Salafi/Jihadist ideology as the main impetus for insurgent violence. Reversing the traditional causal link between violence and religion, this study also demonstrates that the development of Jihadist ideology is a by-product of insurgent mobilization rather than its cause.